2013
DOI: 10.1016/j.jnci.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of minimal residual disease in adult Egyptian patients with precursor acute lymphoblastic leukemia

Abstract: MRD by FCM is a strong independent predictor of outcome in terms of DFS and OS and is a powerful informative parameter in guiding individual treatment in ALL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The cumulative DFS at 2 years for our study group was 43% in comparison to 42% DFS at 2 years in NCI [11], and 64% & 53% reported by others [19] & [20], while the cumulative OS at 2 years for our study group was 46% in comparison to 49% in NCI [11] and 43% at 3-years follow up reported by Larson et al [21].…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The cumulative DFS at 2 years for our study group was 43% in comparison to 42% DFS at 2 years in NCI [11], and 64% & 53% reported by others [19] & [20], while the cumulative OS at 2 years for our study group was 46% in comparison to 49% in NCI [11] and 43% at 3-years follow up reported by Larson et al [21].…”
Section: Discussionsupporting
confidence: 45%
“…The CR rate in our study was 74% compared to 88% in a study done in NCI [11], however their study included patients with both B and T-ALL, while our patients were B-ALL as shown in Table 1.…”
Section: Discussionmentioning
confidence: 57%
“…Several groups showed the predictive value of MRD at the end of induction therapy with low MRD values correlating with better long-term outcome. [10,11] This study demonstrates the feasibility of administering 8 doses of L-asparaginase over two phases rather than over the 4-week period as per the original BFM protocols. This was associated with reduced toxicity and did not compromise the efficacy of the therapy.…”
Section: Discussionmentioning
confidence: 87%
“…All constitutes 30% of all pediatric malignancies and 70% of pediatric leukemia [6]. Minimal residual disease (MRD) studies in childhood acute lymphoblastic leukemia (ALL) give highly significant prognostic information superior to other standard criteria as age, gender and total leucocytic count (TLC) in distinguishing patients at high and low risk of relapse [7]. The approach used in this study was to determine whether panel of antibodies combination are more suitable for detection of MRD in childhood B lineage ALL.…”
Section: Discussionmentioning
confidence: 99%